2007
DOI: 10.1103/physrevlett.98.131103
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Solar Cycle 24 With a Solar Dynamo Model

Abstract: Whether or not the upcoming cycle 24 of solar activity will be strong is being hotly debated. The solar cycle is produced by a complex dynamo mechanism. We model the last few solar cycles by "feeding" observational data of the Sun's polar magnetic field into our solar dynamo model. Our results fit the observed sunspot numbers of cycles 21-23 reasonably well and predict that cycle 24 will be about 35% weaker than cycle 23.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
291
0
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 317 publications
(312 citation statements)
references
References 15 publications
15
291
0
6
Order By: Relevance
“…However it did not take long before another prediction was presented. Choudhuri et al (2007) claimed their model suggests a weak Cycle 24. The models differ in the number of solar cycles they need to make Cycle 24: Choudhuri et al (2007) suggested only one, but indicated several cycles.…”
Section: The Solar Dynamomentioning
confidence: 99%
“…However it did not take long before another prediction was presented. Choudhuri et al (2007) claimed their model suggests a weak Cycle 24. The models differ in the number of solar cycles they need to make Cycle 24: Choudhuri et al (2007) suggested only one, but indicated several cycles.…”
Section: The Solar Dynamomentioning
confidence: 99%
“…This is the first time that predictions in this category are available. The two most complete models (Dikpati, de Toma, and Gilman, 2006;Choudhuri, Chatterjee, and Jiang, 2007) predict high and low solar activity, respectively. Cameron and Schüssler (2007) discuss the progress and problems in using these models for predictions of solar activity.…”
Section: Dynamo Modelmentioning
confidence: 99%
“…Most of the present day predictions are based on statistical analyses of solar activity in the past (Hathaway et al 1999;Hathaway 2009). A more physics-based approach is offered by models of the evolution of the Sun's magnetic field, although recent dynamo computations have given controversial results for cycle 24 (Dikpati & Gilman 2006;Choudhuri et al 2007;Jiang et al 2007). …”
Section: Introductionmentioning
confidence: 99%